Sustainable development: Islamic dimension with special reference to conservation of the environment - Ansari, Abdul Haseeb; Jamal, Parveen; Oseni, Umar Aimhanosi (2011)
Sustainable development is a sine qua non for conservation of the environment and protection of lives of all living creatures on the earth, including the human mass. This was realizes after a considerable loss and sufferance. Allah (s.w.t.) created all components of the environment in a definite proportion with particular tasks assigned to them, and ordained us to maintain that ratio. Disturbing them is considered as a misdeed (fasad), and Allah (s.w.t.) does not like it. The idea of sustainable development is already there in Islam, in the concepts of vicegerency (khalifah) (Islamic brotherhood (ukhuwwah), trust (amanah), public interest (maslahah mursalah), prevention from bad (sadd al-dhari‘ah). The purpose of writing this paper is to pursue an expository study in order to depict the existence of the sustainable development imperative in Islamic injunctions so that it could be an instrument along with other measures for abatement and control of environment degradation and consequential loss due to that.